The Impact Of Sodium Fluoride On Biological Systems, Organs, Tissues, Cells and Sub-cellular Components: A Comprehensive Scientific Review (Comprehensive Journal of Science, 2026)
Background: Sodium fluoride is a widely utilized compound in industrial processes and oral health products, impacting biological systems across multiple hierarchical levels, including organs, tissues, cells, and subcellular structures. While its dental benefits are well established, chronic or excessive exposure disrupts enzymatic activity and function, impairs mitochondrial integrity, and perturbs redox balance, leading to apoptosis, inducing autophagy, and activating inflammatory responses. Understanding these mechanisms is critical for accurate toxicological assessment and for the development of safe, evidence-based applications. Objectives: This review critically evaluates sodium fluoride’s impact across multiple biological levels, from subcellular components to tissues and organs, integrating experimental, clinical, and toxicological evidence. It delineates its chemical properties, exposure pathways, and pharmacokinetics—including absorption, distribution, metabolism, and excretion—while highlighting molecular and cellular mechanisms underlying systemic effects. Dose–response dynamics, exposure duration, and cumulative risk frameworks are examined to distinguish therapeutic benefits from potential toxicity. The review addresses ongoing controversies, methodological limitations, and variability in findings, while discussing protective strategies, public health policies, and ethical and environmental considerations. By synthesizing multidisciplinary evidence, it provides a balanced foundation for safe fluoride use and future research priorities. أسفل النموذج   Conclusion: This review synthesizes current evidence on sodium fluoride’s effects across molecular, cellular, tissue, organ, and systemic levels. Its biological impact is mediated via complex mechanisms, including enzyme modulation, oxidative stress, mitochondrial function, ion transport, and signaling cascades, with outcomes influenced by concentration, exposure duration, and developmental context. Systemic effects involve calcified tissues, endocrine organs, renal systems, and neural structures, with heightened vulnerability during prenatal and early postnatal stages. Risk assessment requires integration of dose–response data, exposure dynamics, and population variability. Evidence-based mitigation, ethical regulation, and interdisciplinary research are essential to optimize therapeutic benefits while minimizing biological and environmental risks.
Keywords: Sodium Fluoride, Chemical Nature, Exposure Pathways, Mechanisms of Action, Biological Systems impact, Organs, Tissues, Cells, Sub-cellular Components, Developmental Considerations, Absorption, Distribution, Neurobiological Processes, Endocrine Interactions, Metabolic Effects, Dose, Duration, Risk Assessment, Protective, Mitigating Strategies, Public Health Policy Implications, Ethical Considerations, Environmental Perspectives